Medical Ethics and Medical Professionalism in Low and Middle Income (LAMIC) Countries: Challenges and Implications. - Coleman, Albert M.E. (Bangladesh Journal of Bioethics, 2015)
This article examines the (bio) ethical and professionalism issues that may arise in the context of medical practice in low and middle income countries (LAMIC), and the challenges this poses for medical regulatory bodies in the regions, in upholding ethics in professional practice. A quadrangle of source of the problems given rise to the breach of ethics in medical practice is identified, and suggested steps, based on ethical principles and concept, is proposed towards the resolution of the problems presented. As LAMIC progress to improve the health of its population, this endeavour should occur hand in hand with contemporary medical ethics theories, taking in context the regions ethnographic and cultural beliefs and practices.